Locally Reprogramming Tumor-Associated Macrophages with Cytokine-Loaded Injectable Cryogels for Breast Cancer - Sydney R. Henriques; Evan B. Glass; Kristen L. Hoek; Ori Z. Chalom; Abigail E. Manning; Sohini Roy; Diana K. Graves; Sarah M. Goldstein; Benjamin C. Hacker; Renjie Jin; Marjan Rafat; Paula J. Hurley; et al. (Annals of Biomedical Engineering, 2025)
Purpose Tumor-associated macrophages (TAMs) are the most abundant immune cells in primary solid tumors, including breast cancer, and typically exhibit an M2-like, immunosuppressive phenotype that promotes tumor growth. Given that TAMs can be repolarized through cytokine signaling, we propose a localized cytokine delivery depot using an injectable alginate cryogel to reprogram TAMs and create an inflammatory, anti-tumor TME. Methods The cryogels were fabricated using cryogelation to generate a macroporous structure, followed by ionic crosslinking to enhance mechanical integrity while preserving pore size distribution. In vitro studies were conducted using bone marrow-derived macrophages, tumor-associated macrophages, and tumor explants. In vivo studies were conducted by orthotopically implanting breast tumors in the fat pads of FVB mice. Cell makeup and tissue composition were analyzed using qRT-PCR, flow cytometry, and Luminex panels. Statistical significance was determined using ANOVA and t -tests. Results In vitro, cryogels released chemokines and cytokines, attracted M2 macrophages, and repolarized them toward M1-like activities. In vivo, cryogel treatment increased the presence of M1 macrophages relative to M2 macrophages in both the primary tumor and lungs, reduced primary tumor growth, and decreased T-cell exhaustion. Conclusions A localized, injectable cryogel depot successfully induces an inflammatory TME, leading to reduced tumor burden and T-cell exhaustion while avoiding systemic toxicities associated with cytokine delivery.

Correction: Locally Reprogramming Tumor-Associated Macrophages with Cytokine-Loaded Injectable Cryogels for Breast Cancer - Sydney R. Henriques; Evan B. Glass; Kristen L. Hoek; Ori Z. Chalom; Abigail E. Manning; Sohini Roy; Diana K. Graves; Sarah M. Goldstein; Benjamin C. Hacker; Renjie Jin; Marjan Rafat; Paula J. Hurley; et al. (Annals of Biomedical Engineering, 2025)